2021
DOI: 10.14527/pegegog.2021.007
|View full text |Cite
|
Sign up to set email alerts
|

Teacher abuse, school burnout and school attachment as predictors of adolescents’ risky behaviors

Abstract: The aim of this study is to determine the predictive level of teacher abuse, school burnout and school attachment for risky behaviors in adolescents, and to examine risky behaviors according to some demographic variables. Relational survey model was employed in the study. The study group consisted of 446 adolescents with an average age of 15.49 years studying in secondary schools. Personal information form, Risky Behaviors Scale, Teacher Emotional Abuse Scale, School Burnout Scale and School Attachment Scale f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…For instance, verbal abuse by the teacher during childhood longitudinally predicted lower self-perceived scholastic competence in adolescence and lower academic achievement for adolescents with low levels of attention problems during childhood (Brendgen et al, 2006) and it decreased the odds of having a high school diploma by the age of 23 for girls (Brendgen et al, 2007). In cross-sectional studies, experiencing emotional violence by teachers was related to lower academic adjustment including grades (Baier et al, 2019), school engagement (Savi Çakar & Uzun, 2021) as well as a higher intention to leave school and lower teacher-rated academic potential (Delfabbro et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, verbal abuse by the teacher during childhood longitudinally predicted lower self-perceived scholastic competence in adolescence and lower academic achievement for adolescents with low levels of attention problems during childhood (Brendgen et al, 2006) and it decreased the odds of having a high school diploma by the age of 23 for girls (Brendgen et al, 2007). In cross-sectional studies, experiencing emotional violence by teachers was related to lower academic adjustment including grades (Baier et al, 2019), school engagement (Savi Çakar & Uzun, 2021) as well as a higher intention to leave school and lower teacher-rated academic potential (Delfabbro et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, teachers’ higher use of verbal and non-verbal reprimands in second grade as assessed through observations predicted a higher increase of peer- and teacher-reported relational aggression of students over the following 3 years (Weyns et al, 2017). Moreover, cross-sectional studies from different cultural settings consistently reported links between emotional violence and more externalizing problems including conduct (Nearchou, 2018; Nkuba et al, 2018a; Pottinger & Stair, 2009) and attention problems (Nearchou, 2018; Nkuba et al, 2018a), aggressive behavior (Kassis et al, 2013; Nkuba et al, 2019) as well as antisocial (Hassandra et al, 2007), risky (Brendgen et al, 2007; Savi Çakar & Uzun, 2021) and delinquent behavior (Martínez-Ferrer & Stattin, 2017; Moon et al, 2009; Moon & Morash, 2013; Nkuba et al, 2019). A few cross-sectional studies considered other mental disorders and found that the exposure to emotional violence by teachers was positively related to posttraumatic stress symptoms (Pottinger & Stair, 2009), personality disorder (Monsvold et al, 2011), suicidality (Lin et al, 2020), substance abuse (Delfabbro et al, 2006), and internet gaming disorder (X.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies suggest that increased experiences of emotional violence are associated with higher prevalence of mental health problems, such as somatization, depression, and posttraumatic stress disorder (Baier et al, 2019; Devries et al, 2014; Mistry et al, 2018; Pottinger & Stair, 2009) and developmental difficulties including low academic performance, risky behaviors, and delinquency (Kızıltepe et al, 2020; Nkuba et al, 2019; Savi Çakar & Uzun, 2021). Brendgen et al (2006) found that students exposed to emotional violence by teachers were at higher risk for delinquent behavior and academic problems in early adolescence.…”
Section: Prevalence and Outcomes Of Emotional Violence By Teachersmentioning
confidence: 99%
“…These studies concentrated on the association between school burnout and academic achievement or academic well-being (Çam & Ögülmüs, 2021;Gabola et al, 2021;Güler & Bedel, 2022, Güngör ,2019Martos Martínez et al, 2021;Özhan & Yüksel, 2021;Parviainen et al, 2021;Rimpelä et al, 2020;Savi Cakar & Uzun, 2021;Teuber et al, 2021;Tomaszek & Muchacka-Cymerman, 2020;Widlund et al, 2020;Yildirim & Koçak, 2022).…”
Section: Correlational Findingsmentioning
confidence: 99%